IN VITRO ANTICANCER, ANTIOXIDANT AND MOLECULAR DOCKING STUDIES OF 4-AMINOBENZAMIDE METAL COMPLEXES - NARASIMHAVARMAN, S.; RAJASEKAR, K.; MANDAL, SUDIP KUMAR; SELVARANI, R.; VEERAVEL, C. (International Journal of Applied Pharmaceutics, 2022)
Objective: Mixed ligand complexes of Cu(II) and Cd(II) with 4-aminobenzamide(4-ABZ) have been synthesized under microwave irradiation and they were characterized by elemental analysis, estimation of metal ion, molar conductivity, magnetic study, FT-IR, Far-IR, electronic spectra, NMR (1H and 13C) and EPR spectral studies. Methods: The data of microanalysis and metal estimation showed that the complexes have the composition of [M(L1)2(L2)2] for Cu(II) and [M(L1)(L2)2] for Cd(II) complex respectively. The conductivity data confirmed the neutral nature of the complexes. The tetrahedral geometry of the Cd(II) complex was confirmed using UV-Visible spectra. The tetragonally distorted octahedral stereochemistry of Cu(II) complex was further confirmed by UV and EPR spectral studies. The diamagnetic nature and probable geometry of Cd(II) complex were also confirmed using NMR spectral studies, which are also compared with free 4-aminobenzamide. The in vitro bio-potential activities of 4-ABA and Cd(II) complex were screened for E. coli and C. Albicans microorganisms by Agar disc diffusion methods. Results: The cancer study of Cu(II) complex and antioxidant activity of DPPH free radical scavenging method of Cd(II) complex were measured and compared with 4-aminobenzamide and standard drugs. The breast cancer studies were also identified using the targeted proteins viz., BRCA1, PR and EGFR by molecular docking study. Conclusion: In the present study, we synthesized new metal complexes of Cu(II) and Cd(II) with 4-ABA and nitrite ion by microwave irradiation method. The analytical data show that the metal-ligand stoichiometry they are non-electrolytes in acetonitrile solution. The spectral data show that the synthesized ligand binds with metal ions through the nitrogen atom of the 4-ABA and oxygen atoms of the nitrite ion.